Intraductal Papillary Mucinous Neoplasms (IPMN): Diagnosis, Classification, and Risk Assessment - A Review of Current Medical Knowledge - Otręba, Karina; Cieszkowska, Joanna; Czupryńska, Karolina; Daniel, Piotr; Leśkiewicz, Michał; Składanek, Justyna (Journal of Education, Health and Sport, 2024)
Introduction In recent years, the widespread utilisation of advanced imaging modalities has led to a surge in the detection rate of pancreatic cystic lesions, particularly intraductal papillary mucinous neoplasms (IPMN). Consequently, this review aims to provide a comprehensive examination of IPMN, focusing on elucidating its intricate facets including definition, epidemiology, pathogenesis, classification, imaging modalities for diagnosis, analysis of pancreatic cyst fluid, evaluation of malignant potential, and identification of pertinent features. Brief Overview of Current Knowledge: IPMN represents a diagnostic conundrum owing to its variable biological behaviour encompassing both benign and malignant spectra, necessitating meticulous evaluation and risk stratification. Various imaging techniques such as MRI, CT, EUS and abdominal ultrasonography serve pivotal roles in the diagnostic algorithm and risk assessment of IPMN. Additionally, the analysis of pancreatic cyst fluid, incorporating biomarkers and the string sign test, assumes a critical role in discerning mucinous from non-mucinous cysts and gauging malignant potential. Discriminating high-risk stigmata and worrisome features serve as a compass for clinical decision-making regarding the imperative of surgical intervention versus vigilant surveillance. Summary Despite persistent challenges, the ongoing evolution of diagnostic modalities and risk assessment methodologies augur well for refining therapeutic strategies and enhancing clinical outcomes in managing IPMN. This review underscores the imperative of sustained research endeavours in the realm of pancreatic oncology to enrich our comprehension of IPMN pathophysiology and to optimise clinical care paradigms.